Ionospheric losses of Venus in the solar wind. Issue 1 (1st January 2020) - Salem, S.; Moslem, W.M.; Lazar, M.; Sabry, R.; Tolba, R.E.; Schlickeiser, R.
Abstract: The nature of ionospheric losses from Venus is of essential importance for understanding the ionosphere dynamics of this unmagnetized planet. A plausible mechanism that can explain the escape of charged particles involves the solar wind interaction with the upper atmospheric layers of Venus. The hydrodynamic approach proposed for plasma expansion in the present study comprises two populations of positive ions and the neutralizing electrons, which interact with the solar wind electrons and protons. The fluid equations describing the plasma are solved numerically using a self-similar approach. The behavior of plasma density, velocity, and electric potential, as well as their reliance upon solar wind parameters have been examined. It is found that for noon midnight sites, the oxygen ion-to-electron relative density may be the main factor to enhance the ionic loss. However, the other parameters, like hydrogen density and solar wind density and velocity seem to do not stimulate the runaway ions. For lower dawn-dusk region, the plasma are composed of hydrogen and oxygen ions as well as electrons, but for higher altitudes only hydrogen ions and electrons are encountered. All ionic densities play an important role either to reduce or boost the ionic loss. The streaming solar wind velocity has no effect on the plasma escaping for lower altitudes, but it reduces the expansion at higher altitudes.